Tridimenzionalna ultrasonografija v diagnostiki skoraj popolne zožitve in zapore notranje karotidne arterije - Tetičkovič, Erih (Zdravniški vestnik, 2001)
Background. Ultrasonographic discrimination of subtotal stenosis from occlusion of the internal carotid artery (ACI) is frequently extremely complicated. Three-dimensional ultrasonography (3D US) is more reliable than color duplex ultrasonography. However, due to possible errors in the evaluation of subtotal stenosis and occlusion, 3D US should be complemented either by three-dimensional CT angiography (3D CTA) or classic angiography. Correct evaluation is extremely important for operative treatment of subtotal stenosis. Methods. In 22 patients, 3D US revealed occlusion of the ACI and in 11 patients subtotal stenosis. In all cases, the ultrasonographic findings were compared with 3D CTA findings, in 8 cases also with those of conventional angiography. Results. In two patients, 3D US evaluated the blockage as an occlusion while 3D CTA as well as angiography showed it to be a subtotal stenosis. In one patient, lumen reduction was so marked that it was not revealed by 3D CTA but only by angiography. In another case, the filiform ACI stenosis was covered by a distinct acoustic shadow of calcinated plaque. When compared, the remaining findings showed no significant differences. Conclusions. It is our opinion that 3D US is a good screening diagnostic method for diagnosing subtotal stenosis and occlusion of the ACI. However, owing to possible errors, it should be combined with 3D CTA or classic angiography. A precise evaluation is very important as subtotal ACI stenosis requires early operative treatment while ACI occlusion only requirers conservative treatment.
Keywords: arterije; Bolezni karotide; Carotid artery diseses; Carotid artery, internal; Carotid stenosis; Diagnosis; Diagnostika; Methods; Metode; Notranja karotida; ožilje; Stenoza; Ultrasonografija; Ultrasonography